The Generative in the Gospel of John: Biblical-theological Reflections on a Philosophical Concept and Attempt of its Liturgical Translation - Bruckner, Isabella (Interdisciplinary journal for religion and transformation in contemporary society, 2024)
The words and expressions used in the Gospel of John represent not only an immediate connection to its philosophical and liturgical context, but also, and precisely for this reason, a challenge for theology. The article deals with the question of the generative in John, focusing particularly on the Prologue of the Gospel. Founded on a theological exegesis of the verses 14 and 18b, it provides fundamental reflections on the femininity of God as well as on a gender-inclusive understanding of the incarnation. The tools used for this argumentation come from philosophy and linguistics. In a second part the biblical analysis result in a translation of these reflections in the field of spiritual practice and aesthetics, respectively liturgy, since “liturgy” is understood, on the one hand, as a public and communitarian act, and on the other hand as the performativity of the Lógos himself mediated by Christian practice.